2008
DOI: 10.1163/156856208783721038
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological evaluation of lactose and chitosan delivered by inhalation

Abstract: Abstract-These days, inhalation constitutes a promising administration route for many drugs. However, this route exhibits unique limitations, and formulations aimed at pulmonary delivery should include as few as possible additives in order to maintain lung functionality. The purpose of this work was to investigate the safety of lactose and chitosan to the pulmonary tissue when delivered by inhalation. The study was carried out with 18 Wistar rats divided in three groups receiving distilled water, lactose or ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…While fibrosis progression is characterised by extracellular matrix (ECM) accumulation and fibroblast proliferation, chitosan is known to inhibit the latter with potent effects on collagen synthesis and ECM production (4,15). TGF-β reportedly plays a crucial role in idiopathic PF and animal models of lung fibrosis (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…While fibrosis progression is characterised by extracellular matrix (ECM) accumulation and fibroblast proliferation, chitosan is known to inhibit the latter with potent effects on collagen synthesis and ECM production (4,15). TGF-β reportedly plays a crucial role in idiopathic PF and animal models of lung fibrosis (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, chitosan obtained from Aspergillus niger is in the process to obtain GRAS status. Chitosan does not present significant toxicity to pulmonary tissue and cells after inhalation [68,69]. In fact, some studies showed some protective effect against oxidative stress [68].…”
Section: Excipients Used In the Development Of Inhalatory Formulationsmentioning
confidence: 99%
“…Chitosan does not present significant toxicity to pulmonary tissue and cells after inhalation [68,69]. In fact, some studies showed some protective effect against oxidative stress [68]. Poly(lactide-co-glycolide) (PLGA) is another biodegradable polymer extensively used in the production of nano-DDS.…”
Section: Excipients Used In the Development Of Inhalatory Formulationsmentioning
confidence: 99%
“…The stability of chitosan-based delivery systems is ensured by strong electrostatic interactions between highly positively charged chitosan amino groups and negatively charged nucleotides (Bhattarai et al, 2010;Katas and Alpar, 2006;Malmo et al, 2012). More importantly, chitosan was reported as non-toxic, biocompatible, biodegradable (Baldrick, 2010) and due to its muco-adhesiveness (de la Fuente et al, 2010), appropriate for nonparenteral administration (de Jesús Valle et al, 2008).…”
Section: Introductionmentioning
confidence: 99%